2021
DOI: 10.1021/acsmedchemlett.1c00134
|View full text |Cite
|
Sign up to set email alerts
|

Macrocyclic Peptides as a Novel Class of NNMT Inhibitors: A SAR Study Aimed at Inhibitory Activity in the Cell

Abstract: Nicotinamide N-methyltransferase (NNMT), which catalyzes the methylation of nicotinamide, is a cytosolic enzyme that has attracted much attention as a therapeutic target for a variety of diseases. However, despite the considerable interest in this target, reports of NNMT inhibitors have still been limited to date. In this work, utilizing in vitro translated macrocyclic peptide libraries, we identified peptide 1 as a novel class of NNMT inhibitors. Further exploration based on the X-ray cocrystal structures of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…Of note, while preparing our manuscript a publication appeared in the literature describing a similar strategy for generating peptidomimetic NNMT inhibitors. 32 Interestingly, the most active peptides identified in that study share very little structural similarity to those identified in our investigations aside from the presence of a number of hydrophobic and positively charged residues. In addition, they appear to inhibit NNMT by binding to the enzyme active site as supported by structural studies.…”
Section: Discussionmentioning
confidence: 61%
“…Of note, while preparing our manuscript a publication appeared in the literature describing a similar strategy for generating peptidomimetic NNMT inhibitors. 32 Interestingly, the most active peptides identified in that study share very little structural similarity to those identified in our investigations aside from the presence of a number of hydrophobic and positively charged residues. In addition, they appear to inhibit NNMT by binding to the enzyme active site as supported by structural studies.…”
Section: Discussionmentioning
confidence: 61%
“…Studies carried out on purified human recombinant protein led to the resolution of a three-dimensional structure and to the identification of main amino acids within the active site [ 40 ]. Moreover, the enzyme kinetic mechanism was elucidated [ 41 ] and this greatly contributed to the design and testing of a variety of NNMT inhibitors [ 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 ].…”
Section: Nicotinamide N -Methyltransferasementioning
confidence: 99%
“…Indeed, with the development of novel synthetic methods, a repertoire of fluorinated prolines dramatically increased during the past two decades. It is impossible to consider in this Perspective each individual example in details, but the list of recent bioactive structures with a fragment of fluorinated proline along with a brief description of their application are outlined in Figure . …”
Section: Application In Medicinal Chemistry and Agrochemistrymentioning
confidence: 99%